Pengembangan Formulasi BIODETERJEN Berbasis Ekstrak Buah Belimbing Wuluh (Averrhoa bilimbi) dan Buah Lerak (Sapindus rarak DC) dengan Penambahan HPMC dan Minyak Esensial Lemon Sebagai Solusi Ramah Lingkungan Terhadap Eutrofikasi - Fadhil Naufal Dzaky; Widayoko, Agus; Yuliani, Yesi (SMA Trensains Muhammadiyah Sragen, 2025)
Eco-friendly biodetergent is a natural detergent made from the bilimbi (belimbing wuluh) and lerak fruits, with the addition of Hydroxypropyl Methylcellulose (HPMC) and lemon essential oil. BIODETERJEN is an alternative solution to reduce the impact of water pollution, especially eutrophication due to chemical detergents that contain harmful compounds, in this case, phosphate. The purpose of this research is to develop and determine the effectiveness of BIODETERJEN made from star fruit and lerak fruit with the addition of HPMC and lemon essential oil. In addition, this research also focuses on efforts to reduce the use of harmful detergents and overcome the eutrophication problem. The method used in this research is descriptive with a quantitative approach and data collection is carried out by observation and literature study, it includes the manufacturing process, formulation, and product testing. The test results include pH test, organoleptic test, foam stability test, and cleaning power test showing that the pH value is 7 (has met SNI 06-3730-1995), foam stability of 85.71% after 10 minutes (has met SNI 06-4085-1996), as well as cleaning power and aroma by the provisions of SNI 06-4085-1996. Besides effectively cleaning stains, this BIODETERJEN is biodegradable, making it safe for the environment. Thus, this BIODETERJEN is an effective alternative solution to reduce the negative impact of chemical detergents on the environment, especially related to eutrophication.